DETECTION AND QUANTIFICATION OF THE EXOS GENE AS A DIAGNOSTIC MARKER CANDIDATE FOR BREAST MILK QUALITY - Anggi Taruli, Jovita
Stunting is a condition of malnutrition closely related to the imbalance of the gut microbiome in infants. The composition of the infant gut microbiome can be influenced by the bacterial community present in breast milk. Some of these bacteria carry virulence factors that can increase the risk of infections, ultimately disrupting the physiological function of the gut, such as inhibiting nutrient absorption processes. Prolonged disruption can lead to malnutrition, including stunting. Currently, the diagnosis of stunting is generally limited to anthropometric measurements comparing the height and weight of infants to those of their peers. Molecular diagnostic approaches can provide a more holistic understanding of stunting through microbiome analysis and the detection of virulence factors in breast milk, the primary food source for infants. In this study, candidate virulence genes from breast milk isolates of mothers with stunted children were identified, including the T3SS effector protein (ExoS) gene commonly found in Pseudomonas aeruginosa. T3SS effector proteins can disrupt cellular signaling activities, altering the tight junction structure in the gut to facilitate pathogen penetration through the epithelial cells, leading to infection. This study aims to: (1) construct the standard curve equation for the quantification of the exoS gene using qPCR; and (2) validate the quantification results of the exoS gene in breast milk samples from mothers with stunted and normal children. Detection of the exoS gene was performed on DNA extractions from pure bacterial isolates (Enterobacter sp. and Brevundimonas sp.) from breast milk using conventional PCR and visualized with 2% agarose gel electrophoresis. Pseudomonas aeruginosa served as a positive control, as it naturally possesses the exoS gene. DNA template preparation for the standard curve quantification of the exoS gene was done by cloning the conserved region of the exoS gene into the pGEM-T Easy vector and amplifying it in E. coli DH5?. The qPCR standard curve was created using a concentration range of 101 to 1010 copy number/?L of the exoS gene, using SYBR Green as the reporter. The standard curve was then used to analyze and compare the copy number of the exoS gene in breast milk samples from mothers with stunted and normal children using qPCR. The results showed that the exoS gene was found in four isolates from the breast milk of mothers with stunted children. The standard curve equation for the quantification of the exoS gene was determined to be y = -3.1458x + 44.676 with an R2 of 95.52% and an efficiency of 107.91%. The qPCR quantification results indicated that the copy number of the exoS gene in breast milk samples from mothers with stunted children was significantly higher compared to those from mothers with normal children.